Risk Factors Associated with Hypothermia in The Newborn Babies Referred to Dr. Moewardi Hospital - Funica Asri Rachmawaty; Dwi Hidayah; Pridania Vidya Ayuningtyas (Fakultas Kedokteran, Universitas Sebelas Maret, 2024)
Background: Hypothermia is a condition when temperature’s body drops drastically, if it occurs in neonates can increases the risk of neonatal mortality. Data on the prevalence of hypothermia in the world reaches 11% - 92% occurring in the community and still being a problem in Dr Moewardi hospital up to 29.9% in 2011. This research interested in finding out more about the risk factors associated with the incidence of hypothermia in referred babies at Dr. Moewardi General Hospital. Method: This research is an observational study using a retrospective cross-sectional design to determine the factors associated with the incidence of hypothermia in referred neonates at the emergency room at Dr. Moewardi General Hospital using total sampling technique. This research analysis uses univariate and bivariate analysis using Statistical Product and Service Solution (SPSS). Results: From the results of chi-square test on the birth weight were found to be significantly related to the incidence of hypothermia in asymptomatic referred neonates, with (p-value) 0.016 (p<0.05). Conclusion: The risk factor associated with the incidence of hypothermia in referred neonates is the birth weight factor.